Examining the relationships between UTAUT2 constructs and mobile banking continuance intention in Sarawak - Latip, Malisah; Kamaruzaman, Muhammad Fadzlan (Universiti Teknologi Mara Cawangan Pulau Pinang, 2026)
Mobile banking has become a vital component of digital financial services; however, sustaining users’ continued engagement remains a challenge, particularly in developing regions. This study examines the relationships between key constructs of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) and continuance intention of mobile banking among users in Bintulu, Sarawak. The study focuses on six constructs: performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, and price value. A quantitative approach was employed using a structured questionnaire administered to 400 mobile banking users. Data were analysed using Spearman’s correlation to assess the strength and direction of relationships between the UTAUT2 constructs and continuance intention. The findings indicate that all six constructs are positively and significantly associated with continuance intention, with effort expectancy and performance expectancy showing the strongest relationships. The study demonstrates the applicability of UTAUT2 in a regional Malaysian context and offers practical insights for banks aiming to support sustained mobile banking usage through enhanced system usability, user support, and value provision.